A comment on Baker et al. 'The time dependence of an atom-vacancy encounter due to the vacancy mechanism of diffusion'. Issue 15 (24th May 2017) - Dasenbrock-Gammon, Nathan; Zacate, Matthew O.
Abstract: Baker et al . derived time-dependent expressions for calculating average number of jumps per encounter and displacement probabilities for vacancy diffusion in crystal lattice systems with infinitesimal vacancy concentrations. As shown in this work, their formulation is readily expanded to include finite vacancy concentration, which allows calculation of concentration-dependent, time-averaged quantities. This is useful because it provides a computationally efficient method to express lineshapes of nuclear spectroscopic techniques through the use of stochastic fluctuation models.